The spectator bird - Stegner, Wallace 1909-1993 (Penguin Books, 2010)
Retired literary agent Joe Allston passes through life as a spectator until he discovers the journals of a trip he took to his mother's birthplace years before.
Keywords: Americans -- Denmark -- Fiction; Marriage -- Fiction; Dänemark; California -- Fiction; Denmark -- Fiction; Domestic fiction; Western stories